The role IL-1 in tumor-mediated angiogenesis - Voronov, Elena; Carmi, Yaron; Apte, Ron N. (Frontiers in Physiology, 2014)
Progressively growing tumors emerge from a unique inflammatory microenvironment derived from the interaction between tumor cells and the host. Tumor angiogenesis is one of the hallmarks of tumor progression and is required for invasiveness and metastasis. Myeloid inflammatory cells, such as immature myeloid precursor cells, also termed myeloid-derived suppressor cells (MDSCs), neutrophils and monocytes/macrophages, are recruited to the tumor microenvironment by factors released by the malignant cells that are subsequently “educated” in situ to acquire a pro-invasive and pro-angiogenic, as well as an immunosuppressive phenotype. The proximity of myeloid cells to endothelial cells (EC) lining blood vessels suggests that they play an important role in the angiogenic response, possibly via secreting a network of cytokines/chemokines and inflammatory mediators. As VEGF is a major angiogenic factor for tumor progression, attempts were made to block the angiogenic response by using anti-VEGF antibodies, or receptor tyrosine kinase inhibitors. Pro-inflammatory mediators were recently shown to play an important role in tumor-mediated angiogenesis and blocking their function can impair tumor progression. Interleukin-1 (IL-1) is an “alarm”, upstream, pro-inflammatory cytokine that is primarily generated by myeloid cells. IL-1 initiates and propagates inflammation, mainly by inducing a local cytokine network and enhancing inflammatory cell infiltration to affected sites and by augmenting adhesion molecule expression on endothelial cells and leukocytes. In this review, we summarize the involvement of IL-1 in tumor-mediated angiogenesis and discuss the future feasibility of IL-1 neutralization approaches in anti-cancer therapy.